2023
DOI: 10.3389/fcell.2023.1125723
|View full text |Cite
|
Sign up to set email alerts
|

Updated perspective of EPAS1 and the role in pulmonary hypertension

Abstract: Pulmonary hypertension (PH) is a group of syndromes characterized by irreversible vascular remodeling and persistent elevation of pulmonary vascular resistance and pressure, leading to ultimately right heart failure and even death. Current therapeutic strategies mainly focus on symptoms alleviation by stimulating pulmonary vessel dilation. Unfortunately, the mechanism and interventional management of vascular remodeling are still yet unrevealed. Hypoxia plays a central role in the pathogenesis of PH and numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…EPAS1/HIF-2α has been proven to have relationship with the TME [73]. Moreover, EPAS1/HIF-2α has also been demonstrated to regulate or take part in many tumor-related pathways, such as the VEGF and PI3K-Akt pathways [74,75]. Furthermore, the degradation of HIF-2α is induced by products of the VHL gene [76].…”
Section: Discussionmentioning
confidence: 99%
“…EPAS1/HIF-2α has been proven to have relationship with the TME [73]. Moreover, EPAS1/HIF-2α has also been demonstrated to regulate or take part in many tumor-related pathways, such as the VEGF and PI3K-Akt pathways [74,75]. Furthermore, the degradation of HIF-2α is induced by products of the VHL gene [76].…”
Section: Discussionmentioning
confidence: 99%
“…WNT7A [445], SLC6A4 [446], BDNF (brain derived neurotrophic factor) [447], CXCL10 [448], NEK7 [449], CYP1B1 [450], ABCA3 [451], TRIB3 [452], PCSK9 [453], FGF2 [454], ACKR4 [455], FASN (fatty acid synthase) [456], VIP (vasoactive intestinal peptide) [457], KL (klotho) [458], BMPR2 [459], APOA1 [323], TLR3 [460], CCR2 [461], TLR7 [462], CAV1 [463], WWC2 [464], TFPI (tissue factor pathway inhibitor) [465], EPAS1 [466] and CCDC40 [467] could serve as a potential therapeutic for pulmonary hypertension treatment. A previous study reported that the genes include CX3CR1 [468], CSF2 [469], CLDN18 [470], TRIM58 [471], PF4 [472], FFAR2 [473], MPO (myeloperoxidase) [474], CD5L [475], SH3GL2 [476], ITGA2B [477], S100A8 [478], VEGFD (vascular endothelial growth factor D) [479], CXCL11 [480], IL1A [481], WNT7A [482], SSTR1 [483], AQP4 [484], SCD (stearoyl-CoA desaturase) [485], SLC6A4 [486], BDNF (brain derived neurotrophic factor) [487], C...…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the interventional management of vascular remodeling is not welldelineated. Hypoxia plays a significant role in the pathogenesis of PAH, and numerous studies have shown the relationship between PAH and the hypoxia-inducible factors family, especially HIF 1A 1,26,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, PAH is categorized into five groups: (i) pulmonary arterial hypertension; (ii) PAH associated with left heart disease; (iii) PAH associated with lung disease and/or hypoxia; (iv) PAH associated with pulmonary artery obstructions; and (v) PAH with unclear or multifactorial mechanisms. The diagnostic criteria for PAH were updated as mean pulmonary artery pressure (mPAP) >20 mmHg at rest during right heart catheterization according to the 2022 European Society of Cardiology/European Respiratory Society PAH guidelines 1,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation